Local characterization of the COVID-19 response: the case of a lockdown in Lusaka, Zambia - Choolwe Muzyamba (BMC, 2021)
Abstract Background The onset of the COVID-19 pandemic has sparked heated debate among scholars on the relevance of lockdowns. There are those in favor of the lockdown and others who are critical of it. However, despite the increased interest in understanding the relevance of lockdowns, there still has not been much focus on its relevance in countries like Zambia. Thus, with the help of the Social Representation Theory (SRT), we set out to explore and document the local characterization of the lockdown by residents of Lusaka, Zambia. Methods We recruited our participants through convenient and purposive sampling techniques. This was done through the use of the ZAMTEL public phone records. Initial contact was made to potential participants, and they were asked of their availability and willingness to participate in the interview. Upon agreeing to participate, they were included in the sample. A total of 68 people were selected to take part in this study. Their age ranged from 20 to 76 years old. 33 of them were male and 35 females. After this, we conducted interviews with the 68 participants. Due to COVID-19 restrictions, our interviews were conducted via telephone in conformity with the recommendations from the IRB in Lusaka and the advice of the ministry of health. We anonymized the demographic characteristics and responses from our participants. Later, thematic analysis was used to analyze the data. Results The lockdown was on one hand lauded for slowing down the incidence rates, preventing fatalities, and protecting the healthcare system from collapse. On the other hand, it was criticized for exacerbating poverty levels, unemployment rates, increasing the rate of mental health problems, aiding gender-based violence, and intensifying political repression and corruption. The results speak to the complexity in the characterization of the lockdown as a response to COVID-19 in Lusaka, Zambia. This observation demonstrates the folly of viewing, applying and characterizing the COVID-19 lockdown as a 'one-size-fits-all' approach in Lusaka, Zambia. Conclusion Rather than establishing the lockdown as an incontestable good, as it is depicted by some scholars or as useless by its critics, our findings instead demonstrate the diversity and complexity in how it is locally viewed by Lusaka residents. The study provides grounds for caution on simplistic and binary characterization of lockdowns. It indicates the need for careful dialog between the designers of lockdowns and citizens in order to tailor such interventions to local realities in context-specific ways. It also shows that though the development of such interventions, all the various and complex elements it embodies must be taken into account in order to realize optimum outcomes.